Estimating actual evapotranspiration through remote sensing techniques to improve agricultural water management: A case study in the transboundary Olifants Catchment in the Limpopo Basin, South Africa - Ahmad, Mobin-ud-Din; Magagula, Thulani F.; Love, David; Kongo, V.; Mul, Marloes L.; Kinoti, Jeniffer (2005)
This paper describes a case study that uses a remote sensing technique, the Surface Energy Balance Algorithm for Land (SEBAL) to assess actual evapotranspiration across a range of land uses in the middle part of the Olifants Basin in South Africa. SEBAL enables the estimation of pixel scale ETa using red, near infrared and thermal bands from satellite sensors supported by ground-based measurements of wind speed, humidity, solar radiation and air temperature. The Olifants River system, although supplying downstream users in Mpumalanga Province (South Africa) and Ch?kw? District (Mozambique), is over-committed, principally for irrigation, in the upper reaches. herefore, quantification of evapotranspiration from irrigated lands is very useful to monitor respect of compliance in water allocations and sharing of benefits among different users. A Landsat7 ETM+ image, path 170 row 077, was acquired on 7 January 2002, during the rainy season and was used for this analysis. The target area contains diverse land uses, including rainfed agriculture, irrigated agriculture (centre pivot, sprinkler and drip irrigation systems), orchards and rangelands. Commercial farming rainfed and irrigated agriculture) is one of the main economic activities in the area. SEBAL ETa estimates vary from 0 to 10 mm/day over the image. Lowest ETa was observed for barren/fallow fields and highest for open water bodies. ETa for vegetative areas ranges 3 to 9 mm/day but irrigated areas, using central pivot, drip and sprinkler systems, appear to evaporate with a higher rate: 6 and 9 mm/day. Penman-Monteith reference crop evapotranspiration ET0 on the same day was found to be 7 mm/day. This indicates that these irrigated areas have no water stress and potential yields can be achieved provided there is no nutrient deficiency. The major finding is that SEBAL results showed that 24% of ETa is from agricultural use, compared to 75% from nonagricultural land use classes(predominantly forest) and only 1% from water bodies. Although irrigation accounts for roughly half of diverted streamflow in the basin, it contributes only about 4% of basin-scale daily ETa at the time of assessment.